Enzymes and membrane proteins of ADSOL-preserved red blood cells - Leonart, Maria Sueli Soares; Nascimento, Aguinaldo José; Nonoyama, Kimiyo; Pelissari, Cinthia Barbosa; Barretto, Orlando Cesar de Oliveira (São Paulo Medical Journal, 2000)
CONTEXT: The preservative solution ADSOL (adenine, dextrose, sorbitol, sodium chloride and mannitol) maintains red cell viability for blood trans-fusion for 6 weeks. It would be useful to know about its preservation qualities over longer periods. OBJECTIVE: To determine some red cell biochemical parameters for peri-ods of up to 14 weeks in order to determine whether the red cell metabo-lism integrity would justify further studies aiming at increasing red cell preservation and viability. DESIGN: Biochemical evaluation designed to study red cell preservation. SETTING: São Paulo University erythrocyte metabolism referral center. SAMPLE: Six normal blood donors from the University Hospital of the Universidade Federal do Paraná, Curitiba, Brazil. MAIN MEASUREMENTS: Weekly assay of erythrocyte adenosine-5´-triphosphate (ATP), 2,3-diphosphoglycerate (2,3DPG), hexokinase (HX), phosphofructokinase (PFK), pyruvate kinase (PK), glucose-6-phosphate dehydrogenase (G-6-PD), 6-phosphogluconic dehydrogenase (6-PGD), glyceraldehyde-3-phosphate dehydrogenase (GAPD), glutathione reduc-tase (GR), glutathione peroxidase (GSHPx), plasma sodium and potas-sium, blood pH, and membrane proteins of red cells preserved in ADSOL were studied during storage for 14 weeks storage. RESULTS: During ADSOL preservation, erythrocyte ATP concentration decreased 60% after 5 weeks, and 90% after 10 weeks; the pH fell from 6.8 to 6.4 by the 14th week. 2,3-DPG concentration was stable during the first week, but fell 90% after 3 weeks and was exhausted after 5 weeks. By the end of the 5th week, an activity decrease of 16-30% for Hx, GAPD, GR, G-6-PD and 6-PGD, 35% for PFK and GSHPx, and 45% for PK were observed. Thereafter, a uniform 10% decay was observed for all enzymes up to the 14th week. The red blood cell membrane pro-teins did not show significant alterations in polyacrylamide gel electro-phoresis (SDS-PAGE) during the 14 weeks. CONCLUSION: Although the blood viability was shown to be poor from the 6th week up to the 14th week of storage due to ATP and 2,3-DPG depletion, the other biochemical parameters remained in fairly good condition for longer storage. As there is a gradual and uniform decay in activity throughout these 14 weeks, it seems that ADSOL-preserved red cells may be used as red cell enzyme standards and membrane proteins as well.